2016
DOI: 10.5539/ijbm.v11n5p296
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Agility: The Key to Organizational Success

Abstract: Background: In the current turbulent and highly competitive environment of today, OA, that is the ability of organizations to quickly sense and respond to environmental changes, is an important determinant of organization success. Purpose:The purpose of this research is to identify the types of OA (sensing agility, decision-making agility and acting agility) and its role in promoting Organizational Success (OS) of the employees at Menoufia University Hospitals in Egypt.Research Design/Methodology: To assess po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…This condition certainly needs improvement, otherwise; it can threaten the survival of SMEs in the future. To survive and win the business in today's increasingly fierce competition, it is very crucial for any kinds of organizations, including SMEs, to have strong organizational agility (Wageeh, 2016;Žitkienė & Deksnys, 2018). Setili (2014) claimed that organizational agility is a critical factor to adapt with the turbulent changes that happen in this disruptive era.…”
Section: Introductionmentioning
confidence: 99%
“…This condition certainly needs improvement, otherwise; it can threaten the survival of SMEs in the future. To survive and win the business in today's increasingly fierce competition, it is very crucial for any kinds of organizations, including SMEs, to have strong organizational agility (Wageeh, 2016;Žitkienė & Deksnys, 2018). Setili (2014) claimed that organizational agility is a critical factor to adapt with the turbulent changes that happen in this disruptive era.…”
Section: Introductionmentioning
confidence: 99%
“…Strangely though the organization should try to simplify workflows, processes and IT systems to prevent adding proprietary complexity to the environmental complex systems and interlinkages (Sherehiy et al, 2007). Practically this means that market or customer structure should be reflected in the organizations departments or even better agile team structures that constantly adapt to the changing outside systems through cross-enterprise collaboration (Baškarada and Koronios, 2018;Wageeh, 2016;Wiraeus and Creelman, 2019). In the same step processes and workflows should always be examined with the purpose to reduce their complexity.…”
Section: Complexitymentioning
confidence: 99%
“…Due to the new nature a responding with gathering information or having slack resources does not prepare an organization to cope with ambiguous issues. Instead ambiguity requires acting agility to external change which converts the situation of the organization (Wageeh, 2016;Zitkiene and Deksnys, 2018). Alternatively an experimentative mindset is required as for example it is not clear how customers will react to a new product or technology (Bennett and Lemoine, 2014).…”
Section: Ambiguitymentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive review of the strategic agility literature shows that strategic agility has positive relationship with and significantly enhances firm performance and that it is a vital factor for organizational success and sustainability in the work environment, as well as the pursuit of excellence, work processes development, and ultimately achieving competitive advantage (Al-Romeedy, 2019; Kwon et al, 2018;Nzewi & Moneme, 2016). It also indicates that strategically agile organisations can be successful in turbulent environments through the abilities of responsiveness, competence, flexibility and speed so that it achieves competitive advantage in the market (Arokodare, Asikhia, & Makinde, 2019;Nafei, 2016;Oyedijo, 2012). Likewise, Tse, Zhang, Akhtar, and MacBryde (2016) revealed that firms that are more concerned about learning are more agile and are more responsive to environmental uncertainties.…”
Section: Environmental Turbulencementioning
confidence: 99%